The comparison between force volume and peakforce quantitative nanomechanical mode of atomic force microscope in detecting cell's mechanical properties. Issue 11 (30th July 2019) - Yang, Yang; Xiao, Xiaoxiao; Peng, Yan; Yang, Chen; Wu, Siqi; Liu, Yuanyuan; Yue, Tao; Pu, Huayan; Liu, Na; Jiang, Haowen
Abstract: Atomic force microscope (AFM) has been widely used in the biological field owing to its high sensitivity (subnanonewton), high spatial resolution (nanometer), and adaptability to physiological environments. Nowadays, force volume (FV) and peakforce quantitative nanomechanical (QNM) are two distinct modes of AFM used in biomechanical research. However, numerous studies have revealed an extremely confusing phenomenon that FV mode has a significant difference with QNM in determining the mechanical properties of the same samples. In this article, for the case of human benign prostatic hyperplasia cells (BPH) and two cancerous prostate cells with different grades of malignancy (PC3 and DU145), the differences were compared between FV and QNM modes in detecting mechanical properties. The results show measured Young's modulus of the same cells in FV mode was much lower than that obtained by QNM mode. Combining experimental results with working principles of two modes, it is indicated that surface adhesion is highly suspected to be a critical factor resulting in the measurement difference between two modes. To further confirm this conjecture, various weight ratios of polydimethylsiloxane (PDMS) were assessed by two modes, respectively. The results show that the difference of Young's modulus measured by two modes increases with the surface adhesion of PDMS, confirming that adhesion is one of the significant elements that lead to the measurement difference between FV and QNM modes. Abstract : The results of this research showed that the FV and QNM modes of AFM provide different elasticity mappings for the same samples respectively. The surface adhesion plays a significant role during the measurement. In addition, the high loading rate may cause an apparent stiffing effect. For this reason, the results of this study will provide a meaningful reference for the selection of the experimental mode of AFM for the soft samples.